A cross-sectional analysis of registered studies on the promising dipeptide carnosine - Pfeffer, Tilman; Wen, Dan; Stefanidis, Konstantinos; Peters, Verena; Ries, Markus (International journal of peptide research and therapeutics, 2023)
Carnosine (β-Alanyl-L-Histidine) is a naturally occurring endogenous dipeptide and over-the-counter dietary supplement with a multimodal mechanism of action. The use of carnosine and its analogues in is as diverse as its mode of action and application. Carnosine’s ready availability and protective properties make it an interesting candidate for clinical use. We have now examined the mode of use in registered clinical studies. In a cross-sectional study, we evaluated the status of clinical studies on carnosine and carnosine analogues. We searched all 16 primary clinical trials registries listed in the WHO Clinical Trials Registry. Registered studies to published studies were identified and the ratio of published/unpublished studies as well as the time to publication and thematic focus were evaluated. The 16 selected registries listed 70 studies on carnosine, of which 34 have been completed and 25 have been published to date, with an average time to publication of 28 months. Carnosine/carnosine analogues were used as dietary supplements in 56% of the studies. Twelve studies were clinical trials in healthy volunteers that focused on dietary changes and underlying physiology. The other 22 studies deal with various clinical pictures, in particular metabolic and psychological disorders. This structured evaluation shows that the applications of carnosine are very versatile, and the registration in one of the clinical registries and the timely publication would facilitate the planning of further studies.
Gesehen am 28.08.2023